Constraints on standard model effective field theory for a Higgs boson produced in association with W or Z bosons in the H → b b ¯ $$ b\overline{b} $$ decay channel in proton-proton collisions at s $$ \sqrt{s} $$ = 13 TeV - The CMS collaboration; V. Chekhovsky; A. Hayrapetyan; V. Makarenko; A. Tumasyan; W. Adam; J. W. Andrejkovic; L. Benato; T. Bergauer; S. Chatterjee; K. Damanakis; M. Dragicevic; et al. (Journal of High Energy Physics)
Abstract A standard model effective field theory (SMEFT) analysis with dimension-six operators probing nonresonant new physics effects is performed in the Higgs-strahlung process, where the Higgs boson is produced in association with a W or Z boson, in proton-proton collisions at a center-of-mass energy of 13 TeV. The final states in which the W or Z boson decays leptonically and the Higgs boson decays to a pair of bottom quarks are considered. The analyzed data were collected by the CMS experiment between 2016 and 2018 and correspond to an integrated luminosity of 138 fb −1. An approach designed to simultaneously optimize the sensitivity to Wilson coefficients of multiple SMEFT operators is employed. Likelihood scans as functions of the Wilson coefficients that carry SMEFT sensitivity in this final state are performed for different expansions in SMEFT. The results are consistent with the predictions of the standard model.